Heterogeneous microoptical structures with sub-micrometer precision - Steenhusen, Soenke; Burmeister, Frank; Gross, Matteo; Domann, Gerhard; Houbertz, Ruth; Nolte, Stefan (Thin Solid Films, 2018)
We demonstrate the fabrication of microoptical elements made from hybrid polymers using two-photon polymerization. To overcome the throughput limitations of two-photon polymerization we use galvanometric mirrors and propose a hatching strategy for rotationally symmetric objects which allows a significant process acceleration to tolerable fabrication times while preserving the surface accuracy of the fabricated elements. Using this strategy and optimized processing parameters we demonstrate the fabrication of an aspheric microlens for diffraction limited focusing which could be fabricated in less than 1.5 min. Thorough topographic characterization with atomic force microscopy and laser scanning microscopy reveal excellent agreement of the fabricated surfaces with the theoretical design with a surface accuracy below 100 nm. Our approach enables the generation of arrays of custom shaped lenses and large arrangements of freeform microoptical elements in a few hours.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Direct-Laser Write; Hybrid Polymer; Microlens; Microoptics; Ormocer; Two-Photon Polymerization